Designing social protection programs - Berhane, Guush; Hirvonen, Kalle (International Food Policy Research Institute, 2018)
The purpose of this chapter is to give policy makers insights into how to design cost-effective social protection programs. Focusing on social assistance (noncontributory transfers to the poor), we review the literature with respect to three key features of the decision to put such a program in place: targeting, choice of payment modality, and graduation.